Characteristics of myeloproliferative neoplasm-associated portal hypertension and endoscopic management of variceal bleeding - Xiaoquan Huang; Ming Zhang; Yingjie Ai; Siyu Jiang; Mei Xiao; Lifen Wang; Yourong Jian; Yuzheng Zhuge; Chunqing Zhang; Shiyao Chen (SAGE Publishing, 2022)
Background: Myeloproliferative neoplasms (MPNs) are a rare yet important clinical cause of portal hypertension, which may cause recurrent gastroesophageal variceal bleeding (GVB). MPN-associated variceal bleeding lacks specific guidelines and clinical consensus and desiderates cohort studies. We performed a multicenter retrospective study to investigate the efficacy of endoscopic management of bleeding in MPNs. Methods: We included consecutive MPN patients with gastroesophageal varices in eight tertiary university hospitals between January 2007 and March 2020. The clinical characteristics of participants were summarized. MPN patients with a history of GVB were followed up for the rebleeding and death, compared with controls suffering from schistosomiasis-associated portal hypertension who received endoscopic treatment for variceal bleeding at the same period. Results: A total of 62 MPN patients with gastroesophageal varices were identified, and 37 had a history of GVB. Of these, 24 patients received endoscopic variceal ligation and endoscopic injection of cyanoacrylate for the prophylaxis of variceal rebleeding. Endoscopic treatment significantly reduced the rebleeding rate in MPN patients with a history of GVB (28.2% versus 68.3%, p  = 0.0269). Multivariable Cox regression indicated that endoscopic treatment (HR = 0.10, 95% CI: 0.02-0.54, p  = 0.008) was the independent protective factor for decreasing the 3-year rebleeding rate, while the use of non-selective beta-blockers (NSBB) (HR = 13.41, 95% CI: 2.15-83.42, p  = 0.005) was the risk factor for increasing the 3-year rebleeding rate. As for the efficacy of endoscopic management, 3-year rebleeding rate was significantly lower in MPN patients in contrast to 46 controls with schistosomiasis-associated variceal bleeding (32.9% versus 59.0%, p  = 0.0346). Conclusion: Endoscopic treatment might be a feasible and potent approach in the management of gastroesophageal variceal rebleeding in MPNs, while NSBB might be ineffective.